D-Cateslytin: a new antifungal agent for the treatment of oral Candida albicans associated infections - Pauline Dartevelle (Nature Portfolio, 2018)
Abstract The excessive use of antifungal agents, compounded by the shortage of new drugs being introduced into the market, is causing the accumulation of multi-resistance phenotypes in many fungal strains. Consequently, new alternative molecules to conventional antifungal agents are urgently needed to prevent the emergence of fungal resistance. In this context, Cateslytin (Ctl), a natural peptide derived from the processing of Chromogranin A, has already been described as an effective antimicrobial agent against several pathogens including Candida albicans. In the present study, we compared the antimicrobial activity of two conformations of Ctl, L-Ctl and D-Ctl against Candida albicans. Our results show that both D-Ctl and L-Ctl were potent and safe antifungal agents. However, in contrast to L-Ctl, D-Ctl was not degraded by proteases secreted by Candida albicans and was also stable in saliva. Using video microscopy, we also demonstrated that D-Ctl can rapidly enter C. albicans, but is unable to spread within a yeast colony unless from a mother cell to a daughter cell during cellular division. Besides, we revealed that the antifungal activity of D-Ctl could be synergized by voriconazole, an antifungal of reference in the treatment of Candida albicans related infections. In conclusion, D-Ctl can be considered as an effective, safe and stable antifungal and could be used alone or in a combination therapy with voriconazole to treat Candida albicans related diseases including oral candidosis.